Instabilidade e sensibilidade de cascas cilíndricas circunferencialmente enrijecidas - Gonçalves, Paulo Batista (1983)
An analysis of the buckling load and the imperfection-sensitivity of ring stiffened cylinders under external pressure is presented. Koiter's general post-buckling theory provides the basis to estimate the imperfection-sensitivity by relating it to the initial post-buckling behavior of the perfect structure. Attention is restricted to cases in which the stiffeners are sufficiently widely spaced for local buckling to be the predominant mode. The stiffeners are light and equally spaced and their bending and torsional stiffness are taken into account. A parametric study was developed and the effect of shell and ring geometric parameters on the buckling load and imperfection-sensitivity was evaluated. Theoretical predictions are compared with available test results and recommended design curves and it is shown that the results here obtained are in good agreement with experimental results. The presented theoretical approach could serve then as a guideline for adequated choice of geometric parameters for design.